Chemical, Biochemical, and Microbiological Properties of Soils from Abandoned and Extensively Cultivated Olive Orchards - A. M. Palese; R. Magno; T. Casacchia; M. Curci; S. Baronti; F. Miglietta; C. Crecchio; C. Xiloyannis; A. Sofo (The Scientific World Journal)
The abandonment of olive orchards is a phenomenon of great importance triggered mainly by economic and social causes. The aim of this study was to investigate some chemical, biochemical, and microbiological properties in a soil of a southern olive grove abandoned for 25 years. In order to define the effect of the long-term land abandonment on soil properties, an adjacent olive grove managed according to extensive practices was taken as reference (essentially minimum tillage and no fertilization). Soil organic matter, total nitrogen, and pH were significantly higher in the abandoned olive grove due to the absence of tillage and the natural inputs of organic matter at high C/N ratio which, inter alia, increased the number of cellulolytic bacteria and stimulated the activity of β-glucosidase, an indicator of a more advanced stage of soil evolution. The soil of the abandoned olive orchard showed a lower number of total bacteria and fungi and a lower microbial diversity, measured by means of the Biolog method, as a result of a sort of specialization trend towards low quality organic substrates. From this point of view, the extensive cultivation management seemed to not induce a disturbance to microbiological communities.